Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian: Survei Rumah Makan Ramayana Solo - Nurfitri Oktaviani; Sumaryanto Sumaryanto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research is a survey of consumers of Ramayana Solo restaurants. The type of data used is quantitative data. The data source used is primary data. The population in this study were consumers who had visited the Ramayana Solo restaurant. The number of samples used in this study were 100 people. This data collection technique uses a questionnaire. This data analysis uses multiple linear regression tests, t tests, F tests, and determination coefficient tests. The t test results show that the price (X1) price has a significant effect on purchasing decisions, product quality (X2) has a significant effect on purchasing decisions and service quality (X3) has a significant effect on purchasing decisions